2020
DOI: 10.3389/fchem.2020.00599
|View full text |Cite
|
Sign up to set email alerts
|

Proximity Effects of Methyl Group on Ligand Steric Interactions and Colloidal Stability of Palladium Nanoparticles

Abstract: Metal nanoparticle catalysts functionalized with small, well-defined organic ligands are important because such systems can provide a spatial control in the catalyst-substrate interactions. This article describes the synthesis, stability, and catalytic property evaluations of four different Pd nanoparticles capped with constitutional isomers of pentanethiolate ligands that have either a straight chain or an alkyl chain with one methyl group at different locations (α, β, or γ from the surface-bound sulfur). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The slower passivation kinetics of ionic head groups in this alternate ligand have allowed for the control of surface ligand density for Pd nanoparticles. The ligand structure, conformation, and surface density on the metal catalyst were also crucial in obtaining the desired activity/selectivity for different catalysis reactions [ 9 , 18 , 19 ]. These Pd nanoparticles synthesized using the thiosulfate protocol have been successfully employed in several organic reactions including, for example, the chemoselective hydrogenation of styrene derivatives, the stereoselective hydrogenation of allenes, the regioselective hydrogenation of dienes, and the regioselective isomerization of allylic alcohols [ 9 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The slower passivation kinetics of ionic head groups in this alternate ligand have allowed for the control of surface ligand density for Pd nanoparticles. The ligand structure, conformation, and surface density on the metal catalyst were also crucial in obtaining the desired activity/selectivity for different catalysis reactions [ 9 , 18 , 19 ]. These Pd nanoparticles synthesized using the thiosulfate protocol have been successfully employed in several organic reactions including, for example, the chemoselective hydrogenation of styrene derivatives, the stereoselective hydrogenation of allenes, the regioselective hydrogenation of dienes, and the regioselective isomerization of allylic alcohols [ 9 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has shown that alkanethiolate-capped PdNPs exhibit excellent catalytic activity and selectivity for isomerization of unsaturated compounds in organic solvents. [26][27][28][29][30][31] This PdNP was synthesized using the thiosulfate protocol with sodium S-alkyl thiosulfate as ligand precursor. Previous studies have shown that the catalytic reactions of hydrophobic PdNPs in aqueous solvent have not been as successful due to the incompatibility of the catalyst and substrate with polar protic solvents.…”
Section: Introductionmentioning
confidence: 99%